Ankyloglossia and its management - Tanay V Chaubal; Mala Baburaj Dixit (Wolters Kluwer Medknow Publications, 2011)
Ankyloglossia or tongue-tie is the result of a short, tight, lingual frenulum causing difficulty in speech articulation due to limitation in tongue movement. In this article, we have reported a 24-year-old male with tongue-tie who complained of difficulty in speech following which he underwent frenectomy procedure under local anesthesia without any complications. Finally, he was given speech therapy sessions.